2024
DOI: 10.1186/s40001-023-01620-7
|View full text |Cite
|
Sign up to set email alerts
|

Biological and glucocorticoids treatment impair the medium-term immunogenicity to SARS-CoV-2 mRNA vaccines in autoimmune inflammatory rheumatic diseases

Silvia Garcia-Cirera,
Joan Calvet,
Juan Francisco Delgado de la Poza
et al.

Abstract: Background This study aims to assess the sustained immunological response to the SARS-CoV-2 vaccine in patients with autoimmune inflammatory rheumatic diseases (AIRD) undergoing different treatment regimens. Methods We conducted a prospective observational study involving 157 AIRD patients without prior COVID-19 infection. Treatment regimens included non-treatment or glucocorticoid-only (not-treated/GCs), non-biological drugs, biological therapy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Among the 13 patients with glucocorticoid monotherapy, the seropositivity rate was 77% [ 8 ]. Similar findings were reported by other studies [ 9 , 10 , 11 , 12 ], including one where inactivated vaccines were also used [ 9 ]. In a study of 597 patients with AIIRD who received homologous inactivated vaccine, Aikawa et al demonstrated that even low doses of prednisolone (5 mg per day) were associated with reduced anti-SARS-CoV-2 S1/S2 IgG positivity (odds ratio (OR) = 0.46, 95% confidence interval (CI): 0.27 to 0.77, p = 0.003) and neutralising antibody positivity (OR = 0.63, 95% CI: 0.44 to 0.90, p = 0.011) [ 13 ].…”
Section: Glucocorticoidssupporting
confidence: 90%
“…Among the 13 patients with glucocorticoid monotherapy, the seropositivity rate was 77% [ 8 ]. Similar findings were reported by other studies [ 9 , 10 , 11 , 12 ], including one where inactivated vaccines were also used [ 9 ]. In a study of 597 patients with AIIRD who received homologous inactivated vaccine, Aikawa et al demonstrated that even low doses of prednisolone (5 mg per day) were associated with reduced anti-SARS-CoV-2 S1/S2 IgG positivity (odds ratio (OR) = 0.46, 95% confidence interval (CI): 0.27 to 0.77, p = 0.003) and neutralising antibody positivity (OR = 0.63, 95% CI: 0.44 to 0.90, p = 0.011) [ 13 ].…”
Section: Glucocorticoidssupporting
confidence: 90%